Iatrogenic Contributions to Cervical Adjacent Segment Pathology: Review Article. Issue 1 (February 2015) - Ueda, Haruki; Huang, Russel C.; Lebl, Darren R.
Background: Anterior cervical discectomy and fusion (ACDF) is widely accepted as a predictably excellent procedure. On the other hand, adjacent level pathology following ACDF is a well-known phenomenon which undercuts surgical outcome. However, the extent to which ACDF accelerates this phenomenon in the naturally degenerating cervical spine is still to be understood. Questions/Purposes: To summarize the current evidence concerning adjacent segment pathology in the light of biomechanics, natural history, postoperative course, and comparison between ACDF and total disc replacement (TDR). Methods: This is a study of published articles. Articles were searched by the topic of adjacent disc pathology in cervical spine through Google Scholar and Pubmed. After review, 37 published articles were deemed suitable for the subject of this study. Results: Biomechanical and clinical data strongly suggest that ASP is a presentation of the iatrogenically accelerated natural aging process of cervical spine. However, power study analysis with assumption showed that current RCTs are unlikely to prove this suggestion. Conclusion: Available data suggests that iatrogenic factors play a significant role in adjacent segment pathology following ACDF.